IMPROVING TEACHERS’ ABILITY IN IMPLEMENTING LEARNING FROM HOME ACTIVITIES DURING THE COVID-19 PANDEMIC THROUGH THE SCHOOL PRINCIPALS’ MONITORING - Ahmad Winarya (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2021)
The purpose of this study was to improve the ability of teachers to carry out learning activities from home during the Covid-19 pandemic through the monitoring from the principal at SDN 1 Purwasari, Kecamatan Cicurug, Kabupaten Sukabumi. The subjects in this study were teachers of SDN 1 Purwasari, Kecamatan Cicurug, Kabupaten Sukabumi. This research utilized school action research using 2 cycles of action. The results of classroom action research indicated that the implementation of principal monitoring was effective in improving teachers’ ability to carry out learning activities from home during the Covid-19 pandemic. In cycle I, the teacher's activities in carrying out learning activities were classified as good with a score of 80.21, but there were still aspects that needed to be improved, especially in the use of media and teaching aids. Meanwhile, in cycle II there was an increase in teachers’ activity to 92.36 with the very good category. In conclusion, the implementation of principal monitoring was effective in increasing the teachers’ ability to carry out learning activities from home during the Covid-19 pandemic so that it could develop an effective learning process at SDN 1 Purwasari, Kecamatan Cicurug, Kabupaten Sukabumi.